A method for preparing multiphase porous ceramics using aluminum ash slag

By desalting the aluminum ash slag and preparing it with silicon and magnesium sources, the problems of resource utilization of aluminum ash slag and high cost of ceramic materials are solved, and harmless treatment of aluminum ash slag and high-performance porous ceramics are realized. Preparation.

CN118184386BActive Publication Date: 2025-02-11INSTITUTE OF MATERIALS & INTELLIGENT MANUFACTURING JIANGXI ACADEMY OF SCIENCES +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410296993.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-15
Publication Date
2025-02-11
Estimated Expiration
2044-03-15

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize aluminum ash slag, which leads to a lack of resource utilization methods. In addition, additional pore-forming agent is required during the preparation of traditional cordierite porous ceramics, which is relatively expensive.

Method used

The aluminum ash slag is desalted by low-temperature rapid leaching method or low-temperature roasting method to obtain the desalted aluminum ash slag, and mixed with the silicon source and magnesium source, ball milling and dry-press forming. Finally, the main phase of cordierite is obtained by roasting. At least one of mullite and magnesium-aluminum spinel is a porous ceramic material of a composite phase.

Benefits of technology

The harmless treatment and resource utilization of aluminum ash slag are realized, the cost of preparing composite porous ceramics is reduced, the processing steps are simplified, and high-performance porous ceramic materials are obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118184386B_ABST
    Figure CN118184386B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of harmless treatment and resource utilization of hazardous solid waste, and in particular to a method for preparing a composite porous ceramic using aluminum ash slag. The present invention first desalts the aluminum ash slag, then mixes it with a silicon source and a magnesium source, and performs ball milling to obtain a mixture; the mixture is dry-pressed to obtain a green body; the green body is sintered to obtain a composite porous ceramic material. The preparation method provided by the present invention directly mixes aluminum ash slag, a silicon source and a magnesium source, and by adjusting the mass ratio of the desalted aluminum ash slag, the silicon source and the magnesium source, ball milling the mixture, pressing and forming, and then sintering, a porous ceramic with cordierite as the main phase and at least one of mullite and magnesium aluminate spinel as the composite phase can be obtained. The method provided by the present invention realizes the harmless disposal and resource utilization of aluminum ash slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of harmless treatment and resource utilization of hazardous solid waste, and in particular to a method for preparing a composite porous ceramic by utilizing aluminum ash slag. Background Art

[0002] Aluminum ash slag is a hazardous solid waste produced after aluminum smelting. Because it contains aluminum nitride and fluorine and chloride salts, it has certain reactivity and leaching toxicity. The hazardous waste code is HW48. At present, the treatment of aluminum ash slag is mainly harmless treatment, and the method of resource utilization is still relatively lacking. Therefore, it is urgent to realize the resource utilization of aluminum ash slag.

[0003] Cordierite porous ceramic materials have good thermal stability, high mechanical strength, large specific surface area, and low thermal expansion coefficient. They are widely used as refractory materials and catalyst carriers. The preparation of traditional cordierite materials mainly uses alumina, magnesium oxide, and silicon dioxide for high-temperature sintering. To sinter cordierite porous ceramics, additional pore-forming agents need to be added. The obtained cordierite porous ceramics have low strength and poor processing performance, which limits their application. The chemical composition of mullite is 3Al2O3·2SiO2, and the chemical composition of magnesia-alumina spinel is Al2O3·MgO, and they have similar sintering temperatures. Alumina, magnesium oxide, and silicon dioxide contained in aluminum ash can form mullite and magnesia-alumina spinel under certain reaction conditions. Mullite has a high melting point, a low thermal expansion coefficient, good high-temperature strength, thermal shock resistance, and creep resistance; magnesia-alumina spinel has good corrosion resistance, high melting point, and good chemical stability, but its expansion coefficient is high and its thermal shock resistance is weak. Therefore, by adjusting the ratio of the above-mentioned materials and the reaction conditions, a variety of porous ceramic materials with cordierite as the main phase and at least one of mullite and magnesia-alumina spinel as the composite phase are prepared, which becomes the direction of resource utilization of aluminum ash slag. Summary of the invention

[0004] The purpose of the present invention is not only to achieve harmless disposal of aluminum ash slag, but also to maximize the utilization of valuable components such as aluminum oxide, magnesium oxide, silicon dioxide, etc. in the aluminum ash slag, and to provide a method for preparing complex porous ceramics using aluminum ash slag, which can realize the resource utilization of aluminum ash slag.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing multiphase porous ceramics by using aluminum ash slag, comprising the following preparation steps:

[0007] Step 1) desalting the aluminum ash slag by a low-temperature rapid leaching method or a low-temperature roasting method to obtain desalted aluminum ash slag;

[0008] Low-temperature rapid leaching method: put aluminum ash into the leaching kettle, the water temperature is lower than 25℃, the water-cement ratio is 6:1, leaching for 4-5 minutes, filter pressing, drying, and obtaining desalted aluminum ash;

[0009] Low-temperature roasting method: put the aluminum ash slag into a high-temperature furnace, heat it to 700℃ at 10℃ / min, keep it warm for 6h, and cool it to room temperature with the furnace to obtain desalted aluminum ash slag;

[0010] The total amount of K, Na, Cl and F in the desalted aluminum ash is less than or equal to 9% of the mass of the aluminum ash powder;

[0011] Step 2) mixing the desalted aluminum ash, silicon source and magnesium source and then ball milling to obtain a mixture;

[0012] Step 3) dry-pressing the mixture to obtain a green body;

[0013] Step 4) drying the green body and then calcining it to obtain a composite porous ceramic material.

[0014] Preferably, in step 2), the silicon source is a silicon-containing material or silicon dioxide; the silicon-containing material comprises silica, quartz or fly ash; the silicon-containing material has a silicon dioxide content greater than 50%; the magnesium source comprises a magnesium-containing material or magnesium oxide; the magnesium-containing material comprises one or more of seawater magnesia and light-burned magnesite; the magnesium oxide content in the magnesium-containing material is greater than 70%.

[0015] Preferably, the particle size of the desalted aluminum ash slag powder particles in step 2) is ≤75 μm.

[0016] Preferably, in step 2), the mass of the silicon source is calculated as the mass of silicon dioxide, and the mass of the magnesium source is calculated as the mass of magnesium oxide; the silicon source accounts for 40-100% of the mass of the desalted aluminum ash slag, and the magnesium source accounts for 5-20% of the mass of the desalted aluminum ash slag.

[0017] Preferably, in step 2), the ball milling uses corundum grinding balls, the material-ball mass ratio is 1:1-5, the ball mill speed is 100-500 rpm, the ball milling is performed alternately in forward / reverse rotation, the frequency is 10-50 min / time, and the ball milling time is 3-10 h.

[0018] Preferably, in step 4), the calcination is performed by heating the green body from room temperature to a first temperature and then to a second temperature, and then keeping the temperature to obtain a sintered body; the sintered body is furnace cooled to room temperature to obtain a composite porous ceramic material; during the calcination process, ventilation is required to maintain air flow; the ventilation rate is 0.2L / min.

[0019] Preferably, the heating rate of the first temperature is 10°C / min, the first temperature is 700°C, the heating rate of the second temperature is 5°C / min, the second temperature is 1250°C, and the insulation time is 2h.

[0020] Preferably, in step 1), waste heat after roasting is used to perform low-temperature desalination or to dry the material after low-temperature rapid leaching.

[0021] The present invention also provides the above-mentioned multi-phase porous ceramic, wherein the multi-phase porous ceramic has cordierite as a main phase and at least one of mullite and magnesia-aluminum spinel as a composite phase.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] First, aluminum ash slag is composed of aluminum, silicon, magnesium oxides, aluminum nitride and salt. The traditional method for treating aluminum ash slag usually makes it into high-aluminum material, which only utilizes the alumina component therein and does not fully realize the resource utilization of aluminum ash slag; the main component of cordierite is 2MgO·2Al2O3·5SiO2. The present invention removes the salt and aluminum nitride in the aluminum ash slag and adds silicon source and magnesium source to obtain the components for preparing cordierite-based ceramics, which maximizes the utilization of aluminum, magnesium, silicon oxides and aluminum nitride in the aluminum ash slag, and realizes the harmless treatment and resource utilization of aluminum ash slag.

[0024] Second, the present invention mixes the desalted aluminum ash with a silicon source and a magnesium source, and by adjusting the mass ratio of the three, ball milling the mixture, pressing and molding, and then calcining, a porous ceramic with cordierite as the main phase and at least one of mullite and magnesium aluminate spinel as a composite phase is obtained. The aluminum nitride in the aluminum ash undergoes an oxidation reaction under oxygen conditions at 700 to 1300°C to generate aluminum oxide and nitrogen, which can play a role in pore formation. No additional pore-forming agent needs to be added, which reduces the cost of preparing composite porous ceramics, simplifies the processing steps of the aluminum ash, and realizes the harmless treatment and resource utilization of the aluminum ash.

[0025] Third, the traditional aluminum ash slag pyrolysis process does not desalinate it. When the salt content in the aluminum ash is high, its melting point will be significantly reduced, resulting in a large amount of liquid phase ( Figure 6 , 7 ), for products ( Figure 5 ) and equipment have a great impact, and the present invention adopts low-temperature roasting or low-temperature rapid leaching method according to the salt content in the aluminum ash slag components to first desalinate the aluminum ash slag. This treatment method can effectively reduce the aluminum ash slag disposal cost, can effectively desalinate while avoiding the complete reaction of aluminum nitride, has a simple process and low cost.

[0026] Fourthly, the present invention can use waste heat to perform low-temperature desalination or dry the material after low-temperature rapid leaching, thereby achieving the effect of energy saving and emission reduction.

[0027] Fifth, the multi-phase porous ceramic material prepared by the present invention can be used as a catalyst carrier, a heat insulating material, a sound insulating material, etc., which is more conducive to the resource utilization of aluminum ash slag. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The morphology of the green body before and after calcination in Comparative Example 1 of the present invention;

[0029] Figure 2 The microstructure diagram of the cordierite / mullite porous ceramic prepared in Example 1 of the present invention;

[0030] Figure 3 The microstructure diagram of the cordierite / magnesium aluminum spinel porous ceramic prepared in Example 2 of the present invention;

[0031] Figure 4 This is an industrial CT photo of the cordierite / mullite porous ceramic prepared in Example 3 of the present invention;

[0032] Figure 5 The macroscopic organization diagrams of the composite porous ceramics prepared in Example 1 (left) and Comparative Example 2 (right) of the present invention;

[0033] Figure 6 This is a graph showing the change in the amount of liquid phase during the calcination of the high-salt aluminum ash slag (1) in Comparative Example 2 of the present invention as a function of temperature;

[0034] Figure 7 This is a curve diagram of the change in the liquid phase amount during the roasting process of low-salt aluminum ash slag in Comparative Example 3 of the present invention as a function of temperature.

[0035] Figure 8 XRD diagrams of the cordierite multiphase porous ceramics prepared in Examples 1 and 2 of the present invention. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing multiphase porous ceramics by using aluminum ash slag, comprising the following preparation steps:

[0037] Step 1) desalting the aluminum ash slag by a low-temperature rapid leaching method or a low-temperature roasting method to obtain desalted aluminum ash slag;

[0038] Low-temperature rapid leaching method: put aluminum ash into the leaching kettle, the water temperature is lower than 25℃, the water-cement ratio is 6:1, leaching for 4-5 minutes, filter pressing, drying, and obtaining desalted aluminum ash;

[0039] Low-temperature roasting method: put the aluminum ash slag into a high-temperature furnace, heat it to 700℃ at 10℃ / min, keep it warm for 6h, and cool it to room temperature with the furnace to obtain desalted aluminum ash slag;

[0040] The total amount of K, Na, Cl and F in the desalted aluminum ash is less than or equal to 9% of the mass of the aluminum ash powder;

[0041] Step 2) mixing the desalted aluminum ash, silicon source and magnesium source and then ball milling to obtain a mixture;

[0042] Step 3) dry-pressing the mixture to obtain a green body;

[0043] Step 4) drying the green body and then calcining it to obtain a composite porous ceramic material.

[0044] In the present invention, the specific operation steps of step 1) are: firstly, the chemical composition of the aluminum ash slag is detected. When the total amount of K, Na, Cl and F in the aluminum ash slag is less than or equal to 9% of the mass of the aluminum ash slag powder, step 2) is directly performed; if the total amount of K, Na, Cl and F in the aluminum ash slag is greater than 9% of the mass of the aluminum ash slag powder, rapid leaching method or low-temperature roasting method desalination treatment is required.

[0045] In the present invention, the silicon source in step 2) is a silicon-containing material or silicon dioxide, preferably silicon dioxide; the silicon-containing material comprises silica, quartz or fly ash, preferably silica or quartz, more preferably silica; the silicon-containing material has a silicon dioxide content greater than 50%, preferably greater than 55%, more preferably greater than 60%;

[0046] The magnesium source comprises a magnesium-containing material or magnesium oxide, preferably magnesium oxide; the magnesium-containing material comprises one or more of seawater magnesia and light-burned magnesite, preferably seawater magnesia; the content of magnesium oxide in the magnesium-containing material is greater than 70%, more preferably greater than 80%, and even more preferably greater than 90%.

[0047] In the present invention, the particle size of the desalted aluminum ash slag powder particles in step 2) is ≤75 μm (200 mesh sieve), preferably ≤63 μm, more preferably ≤53 μm, and even more preferably ≤47 μm.

[0048] In the present invention, the mass of the silicon source in step 2) is calculated as the mass of silicon dioxide, and the mass of the magnesium source is calculated as the mass of magnesium oxide;

[0049] The silicon source accounts for 40-100% of the mass of the desalted aluminum ash slag, preferably 45-90%, more preferably 50-80%, and further preferably 60-70%; the magnesium source accounts for 5-20% of the mass of the desalted aluminum ash slag, preferably 6-15%, more preferably 7-12%, and further preferably 8-10%.

[0050] In the present invention, in the step 2), the ball milling adopts corundum alumina grinding balls, and the mass ratio of the balls is 1:1-5, preferably 1:2-4, and further preferably 1:3; the speed of the ball mill is 100-500 rpm, preferably 150-450 rpm, further preferably 200-400 rpm, and further preferably 250-350 rpm; the ball milling is carried out by alternating forward / reverse rotation, and the frequency is 10-50 min / time, preferably 15-45 min / time, further preferably 20-40 min / time, and further preferably 25-35 min / time; the ball milling time is 3-10 h, preferably 4-9 h, further preferably 5-8 h, and further preferably 6-7 h.

[0051] In the present invention, after obtaining the mixture and before calcining, the process further includes: dry pressing the mixture to obtain a green body; drying and calcining the green body to obtain a multi-phase porous ceramic. In the present invention, dry pressing the mixture before calcining is beneficial for obtaining a multi-phase porous ceramic formed body with a dense structure through one-step calcination.

[0052] In the present invention, the pressure of dry pressing in step 3) is 5 to 200 MPa, preferably 20 to 180 MPa, more preferably 50 to 150 MPa, and further preferably 80 to 120 MPa; the time is 1 to 360 min, preferably 10 to 300 min, more preferably 100 to 250 min, and further preferably 150 to 200 min.

[0053] In the present invention, the calcination in step 4) is to heat the green body from room temperature to a first temperature and then to a second temperature, and keep the temperature to obtain a sintered body; the sintered body is furnace cooled to room temperature to obtain a composite porous ceramic material; ventilation is required to maintain air flow during the calcination process; the ventilation rate is 0.2L / min.

[0054] In the present invention, the heating rate of the first temperature is 10°C / min, the first temperature is 700°C, the heating rate of the second temperature is 5°C / min, the second temperature is 1250°C, and the holding time is 2h. In the present invention, step 1) utilizes the residual heat after roasting to perform low-temperature desalination or dry the material after low-temperature rapid leaching.

[0055] The present invention also provides the above-mentioned multi-phase porous ceramic, wherein the multi-phase porous ceramic has cordierite as a main phase and at least one of mullite and magnesia-aluminum spinel as a composite phase.

[0056] In the present invention, the cordierite porous ceramic material can be used as a catalyst carrier; the cordierite / mullite multiphase porous ceramic material can be used as a filter plate for molten metal; and the cordierite / magnesia-alumina spinel multiphase porous ceramic material can be used as a lightweight thermal insulation material.

[0057] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0058] Preparation Example 1

[0059] The aluminum ash slag was tested for chemical composition. The total amount of K, Na, Cl and F in the aluminum ash slag was less than or equal to 9% of the mass of the aluminum ash slag powder, which was recorded as low-salt aluminum ash slag. The powder composition of the low-salt aluminum ash slag is shown in Table 1, and the aluminum nitride content of the low-salt aluminum ash slag powder is shown in Table 2.

[0060] Preparation Example 2

[0061] The high-salt aluminum ash slag (1) is desalted by a low-temperature rapid leaching method: the aluminum ash slag is placed in a leaching kettle, the water temperature is lower than 25° C., the water-cement ratio is 6:1, leaching is performed for 4 to 5 minutes, filter pressing, and drying to obtain a rapid leaching desalted aluminum ash slag (1);

[0062] The compositions of the high-salt aluminum ash slag (1) and the rapid leaching desalination aluminum ash slag (1) are shown in Table 1, and the aluminum nitride content is shown in Table 2.

[0063] Preparation Example 3

[0064] The high-salt aluminum ash slag (2) is desalted by a low-temperature roasting method: the aluminum ash slag is placed in a high-temperature furnace, heated to 700°C at a rate of 10°C / min, kept at this temperature for 6 hours, and cooled to room temperature with the furnace to obtain roasted desalted aluminum ash slag (2);

[0065] The compositions of the high-salt aluminum ash slag (2) and the roasted desalted aluminum ash slag (2) are shown in Table 1, and the aluminum nitride content is shown in Table 2.

[0066] Table 1 Composition of aluminum ash powder (mass percentage in terms of oxides)

[0067]

[0068] Table 2 Aluminum nitride content of aluminum ash powder (mass percentage)

[0069] Total nitrogen content / % Converted to aluminum nitride content / % Low salt aluminum ash 3.2745 9.586 High salt aluminum ash (1) 2.2531 6.592 Rapid leaching and desalination of aluminum ash (1) 2.1608 6.322 High salt aluminum ash (2) 2.6165 7.655 Roasted desalinated aluminum ash (2) 0.2420 0.708

[0070] Example 1

[0071] (1) Ingredients: Based on the mass of aluminum, silicon and magnesium oxides contained in the rapid leaching desalination aluminum ash (1), and the ratio of each component in the molecular formula of cordierite and mullite (2MgO·2Al2O3·5SiO2 and 3Al2O3·2SiO2), the ingredients are prepared according to the theoretical cordierite / mullite molar mass ratio of 9:1, the analytically pure magnesium oxide accounts for 7.2% of the mass of the aluminum ash, and the silicon dioxide accounts for 42.2% of the mass of the aluminum ash.

[0072] (2) Mixing powder: The proportioned raw materials are ball-milled with a material-ball mass ratio of 1:2. The ball mill speed is 300 rpm. The ball milling is performed alternately in forward and reverse rotations. The time interval between forward and reverse rotations is 15 minutes. The ball milling time is 6 hours. Anhydrous ethanol is added in a 1:1 ratio to the raw material mass and mixed evenly.

[0073] (3) Pressing: The green body was obtained by dry pressing with a pressure of 30 MPa, a sample diameter of 26 mm and a height of 12 mm.

[0074] (4) Drying: Place the green body in a drying oven and dry at 75°C for 8 h.

[0075] (5) Sintering: The green body is placed in a high-temperature furnace for sintering. The sintering conditions are as follows: the high-temperature furnace is heated to 700°C at 10°C / min; then heated to 1250°C at 5°C / min, kept at this temperature for 2 hours, and cooled to room temperature with the furnace to obtain a cordierite / mullite composite porous ceramic material.

[0076] Figure 2 : is the microstructure diagram of the composite porous ceramic. In this embodiment, cordierite / mullite composite porous ceramics are successfully prepared. After sintering at 1250°C for 2h, a large number of needle-shaped mullite phases exist in the pores of the sample, which are interwoven and attached to the matrix cordierite phase.

[0077] Example 2

[0078] The difference from Example 1 is that according to the mass of the oxides of aluminum, silicon and magnesium contained in the rapid leaching desalted aluminum ash (1), and the ratio of the components in the molecular formula of cordierite and magnesium aluminum spinel (2MgO·2Al2O3·5SiO2 and Al2O3·MgO), the ingredients are prepared according to the theoretical cordierite / spinel formation molar ratio of 9:1, the analytically pure magnesium oxide accounts for 8.6% of the mass of the aluminum ash, and the silicon dioxide accounts for 42.7% of the mass of the aluminum ash.

[0079] Figure 3 : is the microstructure diagram of the composite porous ceramic. The cordierite / aluminum-magnesium-spinel composite porous material prepared by sintering at 1250°C for 2h in this embodiment has a large amount of octahedral magnesium-aluminum-spinel phase and blocky cordierite precipitation phase attached to the cordierite matrix.

[0080] Example 3

[0081] The difference from Example 1 is that the calcined desalted aluminum ash slag (2), analytically pure magnesium oxide and silicon dioxide are mixed according to the theoretical cordierite / mullite molar mass ratio of 9:1, the analytically pure magnesium oxide accounts for 12.1% of the mass of the aluminum ash slag, and the silicon dioxide accounts for 47.3% of the mass of the aluminum ash slag.

[0082] Figure 4 This is an industrial CT photo of the cordierite / mullite porous ceramic prepared in Example 3.

[0083] Comparative Example 1

[0084] The only difference from Example 1 is that the proportion of each component is calculated based on the mass of aluminum, silicon and magnesium oxides contained in the rapid leaching desalted aluminum ash (1) and the cordierite molecular formula 2MgO·2Al2O3·5SiO2, and the ingredients are mixed according to the theoretical cordierite composition. The analytically pure magnesium oxide accounts for 8.4% of the mass of the aluminum ash, and the silicon dioxide accounts for 43.9% of the mass of the aluminum ash.

[0085] Comparative Example 2

[0086] The difference from Example 1 is that the high-salt aluminum ash slag (1) is not desalted.

[0087] Figure 5 The effect of desalination treatment on the microstructure and properties of porous cordierite ceramics. Figure 5 The left side shows the porous ceramic material with stable shape and uniform pore distribution obtained by sintering the desalted chloride aluminum ash in Example 2. Figure 5 The right side shows the ceramic material with unstable shape, coarse closed pores and the like obtained after sintering the undesalted high chloride aluminum ash slag of Example 1. Figure 6 The graph of the change of the liquid phase amount during the calcination of the high-salt aluminum ash (1) in Comparative Example 2 is a graph of the change of the liquid phase amount during the calcination process. As the calcination temperature increases, the total amount of liquid phase components of molten salts such as NaF, NaCl, KF and KCl increases sharply after the temperature exceeds 600°C, resulting in a large amount of liquid phase generated during the sintering process, causing the sintering of the composite porous ceramic to fail. Figure 6 .

[0088] Comparative Example 3

[0089] The difference from Example 1 is that the low-salt aluminum ash slag, analytically pure magnesium oxide and silicon dioxide are mixed according to the theoretical cordierite / mullite molar mass ratio of 9:1, the analytically pure magnesium oxide accounts for 8.7% of the mass of the aluminum ash slag, the silicon dioxide accounts for 43.3% of the mass of the aluminum ash slag, and the high-temperature furnace is heated to 700°C at 10°C / min and kept warm for 6 hours.

[0090] Figure 7The graph of the change of liquid phase amount with temperature during the roasting process of low-salt aluminum ash in Comparative Example 3 is shown. As the roasting temperature increases, the total amount of liquid components of molten salts such as NaF, NaCl, KF and KCl increases sharply after the temperature exceeds 700°C. Therefore, keeping at 700°C can effectively desalinate. Figure 7 .

[0091] Table 3 Properties of porous ceramics prepared from aluminum ash

[0092] Bulk density / g / ml Porosity / % Compressive strength / MPa Example 1 0.7714 68.32 12 Example 2 0.8509 63.25 8 Example 3 1.0770 59.26 10 Comparative Example 1 1.4036 45.46 2.8 Comparative Example 3 1.3254 50.78 9

[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing multiphase porous ceramics using aluminum ash slag, characterized in that: The preparation steps include: Step 1) Desalting the aluminum ash slag by a low-temperature rapid leaching method or a low-temperature roasting method to obtain desalted aluminum ash slag; Low-temperature rapid leaching method: putting the aluminum ash slag into a leaching kettle, the water temperature is lower than 25°C, the water-cement ratio is 6:1, leaching for 4 to 5 minutes, filtering by pressure, and drying to obtain desalted aluminum ash slag; Low-temperature roasting method: put the aluminum ash slag into a high-temperature furnace, heat it to 700℃ at 10℃ / min, keep it warm for 6h, and cool it to room temperature with the furnace to obtain desalted aluminum ash slag; The total amount of K, Na, Cl and F in the desalted aluminum ash is less than or equal to 9% of the mass of the aluminum ash powder; Step 2) mixing the desalted aluminum ash, silicon source and magnesium source and then ball milling to obtain a mixture; Step 3) dry-pressing the mixture to obtain a green body; Step 4) drying the green body and then calcining it to obtain a composite porous ceramic material; In step 4), the calcination is to heat the green body from room temperature to a first temperature and then to a second temperature, and then keep the temperature to obtain a sintered body; the sintered body is furnace cooled to room temperature to obtain a composite porous ceramic material; During the roasting process, ventilation is required to maintain air flow; the ventilation rate is 0.2L / min; The heating rate of the first temperature is 10°C / min, the first temperature is 700°C, the heating rate of the second temperature is 5°C / min, the second temperature is 1250°C, and the holding time is 2h; The multiphase porous ceramics are mainly composed of cordierite, and are cordierite / mullite porous ceramics or cordierite / magnesium aluminum spinel porous ceramics.

2. The method for preparing multiphase porous ceramics using aluminum ash slag according to claim 1, characterized in that: In the step 2), the silicon source is a silicon-containing material or silicon dioxide; the silicon-containing material comprises silica, quartz or fly ash; the silicon-containing material has a silicon dioxide content greater than 50%; the magnesium source comprises a magnesium-containing material or magnesium oxide; the magnesium-containing material comprises one or more of seawater magnesia and light-burned magnesite; the magnesium oxide content in the magnesium-containing material is greater than 70%.

3. The method for preparing multiphase porous ceramics using aluminum ash slag according to claim 2, characterized in that: The particle size of the desalted aluminum ash slag powder particles in step 2) is ≤75 μm.

4. The method for preparing multiphase porous ceramics using aluminum ash slag according to claim 1, characterized in that: In the step 2), the mass of the silicon source is calculated as the mass of silicon dioxide, and the mass of the magnesium source is calculated as the mass of magnesium oxide; the silicon source accounts for 40-100% of the mass of the desalted aluminum ash slag, and the magnesium source accounts for 5-20% of the mass of the desalted aluminum ash slag.

5. The method for preparing multiphase porous ceramics using aluminum ash slag according to claim 4, characterized in that: In the step 2), the ball mill uses corundum grinding balls, the material-ball mass ratio is 1:1-5, the ball mill speed is 100-500 rpm, the ball mill is alternately rotated forward / reverse, the frequency is 10-50 min / time, and the ball milling time is 3-10 h.

6. The method for preparing multiphase porous ceramics using aluminum ash slag according to claim 1, characterized in that: Step 1) utilizing the residual heat after roasting to perform low-temperature roasting and desalination or drying the material after low-temperature rapid leaching.

7. A multiphase porous ceramic prepared by the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for preparing foamed geopolymer binding material from aluminum ash and slag

    CN108996930A

  • Method for preparing light porous sintered material from aluminum ash

    CN112430124A

  • Method for preparing refractory material from secondary aluminum ash

    CN115947611A